Corrosion behavior of metal–composite hybrid joints: Influence of precipitation state and bonding zones. (September 2019) - André, Natalia M.; Bouali, Anissa; Maawad, Emad; Staron, Peter; Santos, Jorge F. dos; Zheludkevich, Mikhail L.; Amancio-Filho, Sergio T.
Highlights: Heat-affected zone is more susceptible to corrosion than stir zone due to coarse intermetallic particles and S'(S) phase precipitation. Initial fast strength degradation of the joints: water absorption and NaCl migration into the composite. Strength degradation of the joints was stalled: polymeric layer acted as a protective coating on the aluminum surface. Final strength degradation of the joints: detachment of the polymeric layer and corrosion in joint's core. Abstract: The corrosion behavior of AA2024-T3/carbon-fiber-reinforced polyphenylene sulfide joints was investigated. The joints were exposed to salt spray from one to six weeks. The residual strength of these joints was assessed using lap shear test. The corroded surfaces and interfaces were analyzed using small angle X-ray scattering, scanning electron microscopy, and energy dispersive spectroscopy. Regarding the top surface of the joints, the aluminum part corroded preferably in the heat-affected zone (HAZ). It was demonstrated that the HAZ is more susceptible to corrosion than the stir zone (SZ) due to the anodic sites formed by coarse intermetallic particles and S'(S) phase precipitation. Besides, the macro-galvanic coupling between the zones may also potentialize the corrosion in HAZ as the base material and SZ displayed a lower volume fraction of S'(S) than HAZ. In addition, the corrosion at the interface of the joints was evaluated. Four different stages in the development of corrosion at the interface were identified. At Stage I, the joints showed fast strength degradation (0% to -24% of ultimate lap shear force (ULSF) due to water absorption and NaCl migration into the composite. At Stage II, the strength degradation of the joints was stalled (-24% to -28% of ULSF) due to the protection provided to the bonding area by the reconsolidated layer of polymer at the borders of the joint. The polymeric layer acted as a protective coating on the aluminum surface. At Stage III, the corrosion overcame the polymeric layer by reaching the bonding area of the joint. As a result, the strength of the joints rapidly degraded from -28% to -44% of ULSF. Finally, at Stage IV, one expects generalized corrosion in the bonding area, leading to the final strength degradation of the joint.